2015
DOI: 10.3171/2015.5.focus15162
|View full text |Cite
|
Sign up to set email alerts
|

Discrete or diffuse intramedullary tumor? Contrast-enhanced intraoperative ultrasound in a case of intramedullary cervicothoracic hemangioblastomas mimicking a diffuse infiltrative glioma: technical note and case report

Abstract: Hemangioblastomas are benign, highly vascularized intramedullary lesions that may also extend into the intradural space. Surgery represents the standard therapy, with the goal of obtaining complete resection even at the risk of neurological morbidity. MRI is the gold standard for diagnosis and assessment of intramedullary tumors. Nevertheless, sometimes MRI may not accurately differentiate between different types of intramedullary tumors, in particular if they are associated with syringes or intra- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Systematic research regarding CEUS characteristics of a wider range of CNS tumors will be necessary to adequately determine its role as a useful adjunct for resection of intramedullary spinal tumors. Preliminary case reports by Vetrano et al, 21 Han et al., 22 and our case series suggest that intraoperative CEUS is useful for the assessment of location, borders, and vascularity of intramedullary tumors. In cases of enhancing tumors, CEUS may also help to confirm completeness of initial resection.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Systematic research regarding CEUS characteristics of a wider range of CNS tumors will be necessary to adequately determine its role as a useful adjunct for resection of intramedullary spinal tumors. Preliminary case reports by Vetrano et al, 21 Han et al., 22 and our case series suggest that intraoperative CEUS is useful for the assessment of location, borders, and vascularity of intramedullary tumors. In cases of enhancing tumors, CEUS may also help to confirm completeness of initial resection.…”
Section: Discussionsupporting
confidence: 56%
“…18 Intraoperative contrast-enhanced ultrasound (CEUS) has been proposed as a means of enhancing tumor boundaries to facilitate resection of brain tumors; however, many of these proposals provide a limited pathological scope. [19][20][21][22] Here we present a case series evaluating the intraoperative utility of CEUS in visualizing intramedullary spinal cord tumors with various preoperative MRI characteristics.…”
mentioning
confidence: 99%
“…Authors have previously reported using ultrasound for resection of intramedullary lesions such as tumors and cavernomas, extramedullary lesions such as posttraumatic cysts, placement of syringo-subarachnoid shunts, and also the obliteration of spinal dural arteriovenous fistulae. [10][11][12]14,[16][17][18][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Typically, when preparing for intradural surgery, the bony exposure is planned based on a preoperative CT or MRI. A durotomy is then made by roughly approximating where the lesion should be based on adjacent landmarks.…”
Section: Intradural Mass Lesionsmentioning
confidence: 99%
“…In recent years, the introduction of new intraoperative imaging techniques has considerably changed surgical strategies in neuro-oncology, and these advancements also advanced the mainstays of HB surgery. For example, some studies have shown the role of intraoperative ultrasound (IOUS) in nodule detection [ 14 , 15 ], while contrast-enhanced ultrasound (iCEUS) analysis highlights the tumor and its vascular supply, also in deep-seated areas not directly visible on the brain or spinal cord surface [ 16 ]. Different fluorescent intraoperative dyes have been considered to help identify intramedullary HBs, thus reducing brain and spinal cord manipulation and the risks of postoperative worsening, increasing the extent of resection.…”
Section: Introductionmentioning
confidence: 99%